Oldest Old Long-Term Care Recipients: Findings From the National Center for Health Statistics' Long-Term Care Surveys. (May 2013) - Park-Lee, Eunice; Sengupta, Manisha; Bercovitz, Anita; Caffrey, Christine
The purpose of this study was to examine socio-demographic and health characteristics of the oldest old receiving services from three types of long-term care (LTC) providers. About 45% of nursing home residents in 2004 and 22% of home health care patients and 38% of discharged hospice care patients in 2007 were 85 years and older. The oldest old across the three LTC settings were predominantly White and women. More than two thirds of oldest old nursing home residents, home health care patients, and discharged hospice care patients needed assistance in performing three or more activities of daily living (ADLs) and were bladder incontinent. Hypertension and heart disease were the two most common chronic health conditions that the oldest old LTC recipients had across the care settings. Results provide a baseline that can be used to make comparisons with other new and emerging LTC providers like residential care and home care.